The CARMENES search for exoplanets around M dwarfs: a sub-Neptunian mass planet in the habitable zone of HN Lib - González-Álvarez, Esther; Kemmer, Jonas; Chaturvedi, P.; Caballero, J.A.; Quirrenbach, Andreas; Amado, P.J.; Béjar, V.J.S.; Cifuentes, C.; Herrero, E.; Kossakowski, Diana; Reiners, A.; Ribas, I.; et al. (Astronomy and astrophysics, 2023)
We report the discovery of HN Lib b, a sub-Neptunian mass planet orbiting the nearby ≈$ = 6.25 pc) M4.0 V star HN Lib detected by our CARMENES radial-velocity (RV) survey. We determined a planetary minimum mass of $M_\text{b}\sin i = $ 5.46 $±$ 0.75 $\text{M}_\oplus$ and an orbital period of $P_\text{b} = $ 36.116 $±$ 0.029 d, using $\si
Gesehen am 27.06.2024